IAGE Sdn Bhd a Case Study on Strategic Planning - Adam, Shahzalan (1998)
IA was incorporated twenty two years ago. In 1997, for the first time after it was incorporated IA revenue fell by twelve percent. (Exhibit 1). Encik Rahmat Osman (Rahmat)took over as the Managing Di rector in 1995 and he set out to realign the organization financial affairs when the 1997 financial result was finalized. Rahmat made a special effort to ensure that the Executive Committee spent sufficient time addressing strategic issues. They held a strategy workshop, away from office. He developed a set of ground rules for this session. First, there were not to be extension of the monthly, formal executive committee meeting,so no conformance matters would be raised, indeed no executive decisions would be taken during the workshop. Second, efforts were made beforehand to provide relevant data on the strategic environment of the business I on the customer and competitors as well as the economic, political and social expectation. Third, an external facilitator was used to allow the MD and all executive committee to participate in the discussion. The facilitator then guided the workshop,ensuring everyone contributed, that issues were pursued to the necessary depth and that, finally, a list of action points was prepared.